Probing star formation in the dense environments of z ∼ 1 lensing haloes aligned with dusty star-forming galaxies detected with the South Pole Telescope - Welikala, N; Béthermin, M; Guery, D; Strandet, M; Aird, K; Aravena, M; Ashby, M; Bothwell, M; Beelen, A; Bleem, L; Breuck, C; Brodwin, M; et al. (Oxford University Press, 2015)
We probe star formation in the environments of massive (∼1013 M⊙) dark matter haloes at redshifts of z ∼ 1. This star formation is linked to a submillimetre clustering signal which we detect in maps of the Planck High Frequency Instrument that are stacked at the positions of a sample of high redshift (z > 2) strongly lensed dusty star-forming galaxies (DSFGs) selected from the South Pole Telescope (SPT) 2500 deg2 survey. The clustering signal has submillimetre colours which are consistent with the mean redshift of the foreground lensing haloes (z ∼ 1). We report a mean excess of star formation rate (SFR) compared to the field, of (2700 ± 700) M⊙ yr−1 from all galaxies contributing to this clustering signal within a radius of 3.5 arcmin from the SPT DSFGs. The magnitude of the Planck excess is in broad agreement with predictions of a current model of the cosmic infrared background. The model predicts that 80 per cent of the excess emission measured by Planck originates from galaxies lying in the neighbouring haloes of the lensing halo. Using Herschel maps of the same fields, we find a clear excess, relative to the field, of individual sources which contribute to the Planck excess. The mean excess SFR compared to the field is measured to be (370 ± 40) M⊙ yr−1 per resolved, clustered source. Our findings suggest that the environments around these massive z ∼ 1 lensing haloes host intense star formation out to about 2 Mpc. The flux enhancement due to clustering should also be considered when measuring flux densities of galaxies in Planck data.